Kadar Protein Total dan Ureum Dengan dan Tanpa Penambahan γ-cyclodextrin Pada Serum Lipemik - Sujono, Sujono; Maulida, Yumna Ayu; Sari, Meilanda Puspita (POLTEKKES KEMENKES YOGYAKARTA, 2016)
Lipemic serum is a turbidity serum caused by accumulation of lipoprotein particle. This case distrupt any kinds of examination at clinic laboratory which one of them is examining Total Protein. It can be carried out by adding γ-cyclodextrin in order to handle the turbidity on lipemic serum. This study aims at finding the Total Protein’s levels overview on lipemic serum with and without addition of γ-cyclodextrin. This study was pre-eksperimental design byusing Post Test Only with Control Group Design. This study was done at Chemistry Laboratory, Health Analysis Study Program in April 2016. The sample of the data was 20 lipemic serum. In examining of total proteis’s level used Biuret method and ureum level used Barthelot method from lipemic serum with and without addition ofγ-cyclodextrin 20%.There is a significant difference between total protein and ureum, the difference average of total protein level and ureum level before and after adding γ-cyclodextrin was 1,311 g/dL (12,40%) and 6.38 mg/dL (10.88%).